2020
DOI: 10.1038/s41598-020-78614-6
|View full text |Cite
|
Sign up to set email alerts
|

2D nanosheets and composites for EMI shielding analysis

Abstract: Liquid exfoliated, 2-dimensional (2D), few layered graphene and molybdenum disulfide nanosheets (GNS and MNS) are size selected for EMI shielding application. Scanning electron microscopy (SEM) has confirmed the lateral dimensions increase (1–2 µm for GNS and MNS) with lowering centrifugation speed (1000 to 500 rpm). The micron size (~ 15 µm) restacked structures of GNS and MNS (L ~ 2 µm) over a nylon membrane have shown ~ 16 dB and ~ 6 dB EMI shielding effectiveness (1–8 GHz frequency), respectively. The enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…These losses increase not only with the GNP content but also with the surface area, as it has been recently reported [ 31 ]. A higher aspect ratio raises the percolation network (in this case, the larger the specific area, the higher the aspect ratio), which means that it has a higher electrical conductivity and thus increases the EMI shielding effectiveness [ 57 ]. It is important to note that this increase in shielding due to the increase in the electrical conductivity by the introduction of carbonaceous reinforcements can be preferably caused by reflection; however, the most desirable is to generate an adequate impedance mismatch to avoid these losses due to reflection and to increase the absorption losses, for example, by adding ferrites [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…These losses increase not only with the GNP content but also with the surface area, as it has been recently reported [ 31 ]. A higher aspect ratio raises the percolation network (in this case, the larger the specific area, the higher the aspect ratio), which means that it has a higher electrical conductivity and thus increases the EMI shielding effectiveness [ 57 ]. It is important to note that this increase in shielding due to the increase in the electrical conductivity by the introduction of carbonaceous reinforcements can be preferably caused by reflection; however, the most desirable is to generate an adequate impedance mismatch to avoid these losses due to reflection and to increase the absorption losses, for example, by adding ferrites [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Khan et al. 34 found an EMI effectiveness of 18 dB with graphene- and MoS 2 -based materials. The EMI shielding of the MoS 2 -rGO/Fe 3 O 4 nanostructure was assessed in the 8–12 GHz range by Prasad et al 35 and was 8.27 dB.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Zhang et al 33 reported sulfonated reduced less defect graphene oxide (S-rLGO) combined with P(St-BA) latex through blending and casting processes and reported an overall shielding effectiveness of 16 dB. Khan et al 34 found an EMI effectiveness of 18 dB with graphene-and MoS 2 -based materials. The EMI shielding of the MoS 2 -rGO/Fe 3 O 4 nanostructure was assessed in the 8−12 GHz range by Prasad et al 35 and was 8.27 dB.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Khan et al [ 107 ] reported that they used the liquid‐phase exfoliation method to reduce the bulk of MoS 2 to 2D NSs. They were able to make the lateral dimensions of the NSs bigger by lowering the centrifugation speed from 1000 to 500 rpm.…”
Section: Tmdcs: Microwave Absorption and Emi Shieldingmentioning
confidence: 99%